Pemanfaatan Ekstrak Belimbing Wuluh (Averrhoa bilimbi) dengan Penambahan Kitosan dari Limbah Kulit Udang sebagai Cairan Pembersih Toilet - Fawaz Fawzan; Ektada Benezham Muhammad; Widayoko, Agus; Hidayani, Yuni (SMA Trensains Muhammadiyah Sragen, 2025)
The toilet floor is a surface that is frequently contacted by human feet, making it an ideal environment for the proliferation of germs and bacteria. One frequently utilized antibacterial compound is chitosan, which is derived from shrimp shells. However, the unmanaged disposal of shrimp shell waste has the potential to cause environmental issues. The objective of this study is to utilize Averrhoa bilimbi extract as a base material for a toilet cleaning liquid, with the addition of chitosan derived from shrimp shell waste. This research concept employs chitosan derived from shrimp shells, which exhibits antimicrobial properties and has the potential to serve as a cleaning agent, in conjunction with Averrhoa bilimbi extract, which is rich in citric acid and functions as a natural cleaning agent. The research design is descriptive and employs a qualitative comparative approach. The ratios of Averrhoa bilimbi extract and baking soda to chitosan were varied, including 25:1:1, 25:1:2, and 25:1 (with no chitosan as a control). The findings indicated that all cleaning liquid samples satisfied the pH standard outlined in SNI 1842:2019. The sample with the ratio of baking soda, Averrhoa bilimbi, and chitosan at 1:25:2 exhibited the optimal level of cleanliness and the most concentrated aroma. This study demonstrates that Averrhoa bilimbi extract can serve as an environmentally sustainable toilet cleaning agent when combined with shrimp shell waste.